Cerebral near-infrared spectroscopy in term newborns: reference values and hypoxic-ischemic encephalopathy - Gumulak R; Nandraziova L; Tulejova L; Pazicka Z (Acta Medica Martiniana, 2019)
Non-invasive measurement of cerebral tissue oxygenation (cStO2) using near-infrared spectroscopy (NIRS) is attracting an increasing attention not only in neonatology. The vast diversity of commercially available NIRS devices makes it difficult to compare in the published clinical studies. This review provides a view on the practical use of NIRS as a tool for cStO2 measurement, its limitations and pitfalls, with a focus on brain dysfunction caused by hypoxic-ischemic encephalopathy. This syndrome of disturbed neurologic function in the earliest days after the birth in the term infants is manifested by difficulty with initiating and maintaining respiration, depression of tone and reflexes, subnormal level of consciousness, and often seizures. This fascinating technology has already proven accurate and has been recommended to use during daily routine tool to evaluate the level of oxygen saturation in brain in intensive care units worldwide.